Effectiveness of Learning Outcomes through Problem-Based Learning Model Utilizing Augmented Reality (AR) Technology in Grade IV Material on the Form of Matter and its Changes in the Ki Hadjar Dewantara Group - Indira Rachmayani; Novi Setyasto (Postgraduate, University of Mataram, 2025)
The use of learning models and media that are not in accordance with the Process Standards contained in Permedikbudristek Number 16 of 2022. This type of research is experimental research with a Quasi Experimental design in the form of Nonequivalent Control Group Design. The population of this study was all students of class IV of SD Gugus Ki Hadjar Dewantara totaling 82 students. The sampling technique was purposive sampling. In this study, SD Muhammadiyah Purwodadi class IV Al-Majid as the experimental class and class IV Al-Qowiyuu as the control class. Data collection techniques were in the form of test techniques (pretest and posttest); non-test techniques, namely observation, interviews, questionnaires, and documentation. Initial data analysis techniques include normality and homogeneity tests and final data analysis with t-test and N-Gain. The output of the t-test is a sig. value of 0.002 (sig. <0.05), so H0 is rejected and Ha is accepted. The output of the N-Gain test for the experimental class is 0.67 and the control class is 0.42. In conclusion, the AR-assisted PBL model is effective in improving student learning outcomes compared to the PBL model version of the teacher assisted by the media of science images for grade IV SD Gugus Ki Hadjar Dewantara.